2015
DOI: 10.1001/jamadermatol.2014.2229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Total-Body Digital Photography on Cancer Worry in Patients With Atypical Mole Syndrome

Abstract: Patients with AMS have low levels of melanoma-related worry, which is similar to data from other populations at high risk of cancers. We found that TBDP is a clinically useful tool that can be used in PLCs to help decrease worry about developing melanoma in at-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Secondary measures and outcomes (measured at baseline, 6 and 12 months) include: demographics and clinical variables: age, gender, marital status, postcode, highest education level, occupation, history of skin cancer (melanoma, squamous cell carcinoma, basal cell carcinoma), skin and hair type (density of freckles on arms before age 20, natural hair colour at age 15, number of severe sunburns aged 2–18), number of raised moles on both arms, measured at baseline only, 21 22 collected as part of the baseline eligibility assessment; sun protection habits scale developed by Glanz et al in the USA for a multicomponent skin cancer prevention programme; this comprises five items measured using a four-point Likert scale, and relating to use of sun protection, sun and sunbed habits, and episodes of sunburn in the previous year, 28 as we hypothesise that the App reminders will prompt people and reinforce the messages on sun protection; skin self-examination benefits and barriers scale: validated by Manne and Lessin in the USA among melanoma survivors, and developed from previous work on mammography and family members of patients with colorectal cancer. 29 The benefits scale has seven items (α=0.71) and the barriers scale has 10 items (α=0.74); Melanoma Worry Scale (MWS) validated by Moye et al in the USA, 30 and adapted from the Breast Cancer Worry Scale; 31 this measure comprises four items, scored 1 to 4, with possible scores ranging from 4 to 17, and higher scores indicating higher levels of worry Perceived melanoma risk: drawn from Manne and Lessin’s measures, 29 these two items have been widely used for melanoma and other cancer risk assessments to assess estimated percent risk of developing melanoma, and perceived risk compared with a person of the same age (relative risk); Self-efficacy for consulting without delay: A 10-item self-completed scale summed to score 10–100, was used in a primary care trial for lung symptoms and showed good internal reliability (Cronbach α=0.85). 32 33 It has been adapted for this trial, and reduced to eight items, for example.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary measures and outcomes (measured at baseline, 6 and 12 months) include: demographics and clinical variables: age, gender, marital status, postcode, highest education level, occupation, history of skin cancer (melanoma, squamous cell carcinoma, basal cell carcinoma), skin and hair type (density of freckles on arms before age 20, natural hair colour at age 15, number of severe sunburns aged 2–18), number of raised moles on both arms, measured at baseline only, 21 22 collected as part of the baseline eligibility assessment; sun protection habits scale developed by Glanz et al in the USA for a multicomponent skin cancer prevention programme; this comprises five items measured using a four-point Likert scale, and relating to use of sun protection, sun and sunbed habits, and episodes of sunburn in the previous year, 28 as we hypothesise that the App reminders will prompt people and reinforce the messages on sun protection; skin self-examination benefits and barriers scale: validated by Manne and Lessin in the USA among melanoma survivors, and developed from previous work on mammography and family members of patients with colorectal cancer. 29 The benefits scale has seven items (α=0.71) and the barriers scale has 10 items (α=0.74); Melanoma Worry Scale (MWS) validated by Moye et al in the USA, 30 and adapted from the Breast Cancer Worry Scale; 31 this measure comprises four items, scored 1 to 4, with possible scores ranging from 4 to 17, and higher scores indicating higher levels of worry Perceived melanoma risk: drawn from Manne and Lessin’s measures, 29 these two items have been widely used for melanoma and other cancer risk assessments to assess estimated percent risk of developing melanoma, and perceived risk compared with a person of the same age (relative risk); Self-efficacy for consulting without delay: A 10-item self-completed scale summed to score 10–100, was used in a primary care trial for lung symptoms and showed good internal reliability (Cronbach α=0.85). 32 33 It has been adapted for this trial, and reduced to eight items, for example.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Melanoma Worry Scale (MWS) validated by Moye et al in the USA, 30 and adapted from the Breast Cancer Worry Scale; 31 this measure comprises four items, scored 1 to 4, with possible scores ranging from 4 to 17, and higher scores indicating higher levels of worry…”
Section: Methods and Analysismentioning
confidence: 99%
“…Participants will complete a questionnaire collecting quality of life (EQ-5D-5L [29]), anxiety and depression (HADS [30]), worry about melanoma (Melanoma Worry Scale) [31]), self-report of health service use, self-report of TSSE practice (frequency and coverage), and ratings of intention, selfefficacy and planning over future TSSE. [32] Follow up…”
Section: Baselinementioning
confidence: 99%
“…Total body photography (TBP) has been associated with detection of thin melanomas, fewer biopsies and decreased patient anxiety . While detection of thinner melanomas is a surrogate for survival benefit, whether TBP is associated with improved survival has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Total body photography (TBP) 1 has been associated with detection of thin melanomas, 2-6 fewer biopsies 5 and decreased patient anxiety. 7 While detection of thinner melanomas is a surrogate for survival benefit, 8 whether TBP is associated with improved survival has not been examined. Demonstrating survival benefit from early melanoma detection is problematic given its low incidence, and most melanomas are diagnosed as early-stage lesions associated with long-term survival.…”
Section: Introductionmentioning
confidence: 99%